PERLINDUNGAN HUKUM BAGI NASABAH DEBITUR TERHADAP PENETAPAN BUNGA BANK YANG TIDAK SESUAI DENGAN PERATURAN PERUNDANG – UNDANGAN DALAM PERJANJIAN KREDIT - Priyambodo, Sigit (Program Pascasarjana Universitas Sunan Giri Surabaya, 2019)
The purpose of this study is to analyze the determination and calculation of bank interest in conflict with applicable laws and regulations and analyze the legal protection of debtors as credit recipients in a credit agreement. Data collection techniques in the form of document studies, namely conducting research on documents relating to the problem to be examined in order to obtain a theoretical foundation and information in the form of formal provisions. The materials obtained were analyzed using qualitative normative methods. The results showed that the calculation of Prime Lending Rate was contrary to article 1767 paragraph 3 of KUHP. State Gazette number 22 of 1848 so that it does not provide legal certainty to people who want to receive credit from banks to develop their businesses. The form of legal protection to debtors against credit based on article 1323 of the Civil Code The agreement made between the bank as the lender and the customer as the recipient of the credit is null and void by law and based on article 1166 provides legal protection as the owner of the object. It is expected that when reading the clause regarding the determination of bank interest by banks, it should be observed first the laws and regulations concerning the determination of credit.